An assessment of students’ attitudes toward wrongful convictions / Bala Usman Chamo - Chamo, Bala Usman (2014)
The study attempts to assess students‟ attitudes toward wrongful convictions. It tried to replicate Ricciardelli, Bell and Clow‟s (2009) Canadian study using an undergraduate student sample from the United Kingdom. This will help to understand whether the students‟ attitudes toward wrongful convictions differ between the two studies. This study adopts a between group design, in which one 150 participants were involved. The attitudes of 81 Criminal justice students and 69 Noncriminal Justice Students were compared. The study also assessed students‟ attitudes according to year of study, in which 74 year one students‟ were compared with 71 year three students. Additionally, attitudes were examined according to gender. The findings revealed that criminal justice students differ from noncriminal justice students in their attitudes toward wrongful convictions. Years three gave higher estimates of the frequency of wrongful convictions and were more supportive for the Blackstone ratio than year one students. Nevertheless, year one students were more supportive of the need to train the criminal justice professionals than year three students. The result showed no difference between the participants‟ confidence in the criminal justice system. No differences were found between males and female in terms of their attitudes toward wrongful convictions. The implications of the findings were discussed. Maximum of 250 words.